Circocus, Liquid Organic Eco-Enzymes As A Utilization Of Citrus Waste In Dau District - Ayu Nayla Azzahra; Chelsy Aila Agustin; Devina Alya Syifa; Saira Asalina Rasida; Zerlina Nariswari Wisena; Dalilah Apria Ningsih (Kolej PERMATA Insan, 2025)
Insan Junior Researcher International Conference & Innovation (iJURECON) 2025 : “STREAM for a Better Future/ editor : Ahmad Fuad Mohamad Amin, Nurul Shazwani Binti Mohamed, Rossidi Bin Usop, Abdel Rahman Ibrahim Suleiman Islieh Organised by Kolej PERMATA Insan 10-11 October 2025